The Use of GIS Technology in Recording and Creating a Database of Agricultural Land in Bulungur District - Shermatovich, Umarov Nurali; Ramonovich, Yarkulov Zokir (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the use of the database. Currently, as a result of the cadastral database, the focus is on implementing these processes with technical tools equipped with special software capable of creating, storing, updating and, if necessary, analysing and processing the data collected.